Demineralized Cortical Bone Matrix Augmented With Peripheral Blood-Derived Mesenchymal Stem Cells for Rabbit Medial Meniscal Reconstruction - Mao, Beini; Zhang, Zhong; Lai, Sike; Zhang, Kaibo; Li, Jian; Fu, Weili (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue engineering is a promising treatment strategy for meniscal regeneration after meniscal injury. However, existing scaffold materials and seed cells still have many disadvantages. The objective of the present study is to explore the feasibility of peripheral blood-derived mesenchymal stem cells (PBMSCs) augmented with demineralized cortical bone matrix (DCBM) pretreated with TGF-β3 as a tissue-engineered meniscus graft and the repair effect. PBMSCs were collected from rabbit peripheral blood and subjected to three-lineage differentiation and flow cytometry identification. DCBM was prepared by decalcification, decellularization, and cross-linking rabbit cortical bone. Various characteristics such as biomechanical properties, histological characteristics, microstructure and DNA content were characterized. The cytotoxicity and the effects of DCBM on the adhesion and migration of PBMSCs were evaluated separately. The meniscus-forming ability of PBMSCs/DCBM complex in vitro induced by TGF-β3 was also evaluated at the molecular and genetic levels, respectively. Eventually, the present study evaluated the repair effect and cartilage protection effect of PBMSCs/DCBM as a meniscal graft in a rabbit model of medial meniscal reconstruction in 3 and 6 months. The results showed PBMSCs positively express CD29 and CD44, negatively express CD34 and CD45, and have three-lineage differentiation ability, thus can be used as tissue engineering meniscus seed cells. After the sample procedure, the cell and DNA contents of DCBM decreased, the tensile modulus did not decrease significantly, and the DCBM had a pore structure and no obvious cytotoxicity. PBMSCs could adhere and grow on the scaffold. Under induction of TGF-β3, PBMSCs/DCBM composites expressed glycosaminoglycan (GAG), and the related gene expression also increased. The results of the in vivo experiments that the PBMSCs/DCBM group had a better repair effect than the DCBM group and the control group at both 12 and 24 weeks, and the protective effect on cartilage was also better. Therefore, the application of DCBM augmented with PBMSCs for meniscus injury treatment is a preferred option for tissue-engineered meniscus.